Protective effects of insulin on dry eye syndrome via TLR4/NF-κB pathway: based on network pharmacology and in vitro experiments validation - Yuan, Xiuxiu; Zhang, Yu; Wang, Siyi; Du, Zhiyu (Frontiers in Pharmacology, 2024)
Dry eye syndrome (DES) is a multifactorial ocular surface disease and represents one of the most prevalent ophthalmic disorders. Insulin is an important metabolism-regulating hormone and a potential antioxidant with critical biological roles as anti-inflammatory and anti-apoptotic. However, its mechanism of action remains unknown. In this study, we used network pharmacology techniques and conducted cell experiments to investigate the protective effect of insulin on human corneal epithelial cells (HCECs). Eighty-seven common targets of insulin and DES were identified from the database. KEGG pathway enrichment analysis suggested that insulin may be crucial in regulating the toll-like receptor (TLR) signaling pathway by targeting key targets such as IL-6 and TNF. In cell experiments, insulin promoted HCECs proliferation, improved their ability to migrate, and inhibited apoptosis. Western blot and enzyme-linked immunosorbent assay (ELISA) also confirmed the upregulation of the expression of inflammatory factors such as IL-1β, IL-6, and proteins related to the TLR4/NF-κB signaling pathway. However, the expression of these proteins was inhibited by insulin administration. Our results preliminarily verified insulin may exert a protective role on HCECs under hyperosmotic condition, which offered a novel perspective for the clinical management of this condition.